Pyogenic Granuloma of Inferior Turbinate in Children: Common Symptoms with a Rare Diagnosis - Nor Eyzawiah Hassan; Siti Nur Farhana Ariff; Shahrul Hitam; Nor Azirah Salahuddin; Siti Asmat Md Arepen (USIM Press, 2024)
Vol. 7 No. 3 (2021): Special Issue on Clinical Scenarios In Medicine, A Malaysian Experience (Case Report)